Ethnographic Study Of Svaneti (Recordings Of Evdokia Kozhevnikova) - Khizanishvili, Manana; Tserediani, Nino; Chamgeliani, Madona (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2017)
Georgian national museum, Simon Janashia museum of Georgia preserves ethnographic records and visual material, photographs and drawings of household items performed by ethnologist Evdokia Kozhevnikova – a graduate of St. Petersburg University and a student of Nicholas Marr. Her works hold some of the most exclusive data about ethnographic lifestyle of the Svan people during the 1920s-1940s. The theme of her recordings is diverse and includes religious festivals and magic mastery, folklore, folk law, hunting, funeral and mourning traditions, parenting rules, etc. In addition to describing the events, Evdokia in some cases tries to analyze and study the particular stories. The ethnographic data of Evdokia Kozhevnikova is especially relevant and important today, as the elements of ethno-cultural heritage are gradually disappearing and being forgotten. Therefore, the photographs and other recordings which illustrate the way of life of the Svan people are extremely valuable. The aim of this article is to introduce the scholars and all the interested people to the ethnographic records of Dina Kozhevnikova-Gugushvili – a lady, insanely in love with Svaneti, and to reveal her interesting analysis regarding some issues, including St. George, and sacrifice traditions to the deity of the land.